Evaluation of Alveolar Bone Quality: Correlation Between Histomorphometric Analysis and Lekholm and Zarb Classification - Oliveira, Marina Reis [UNESP]; Gonçalves, Andréa [UNESP]; Gabrielli, Marisa Aparecida Cabrini [UNESP]; de Andrade, Cleverton Roberto [UNESP]; Vieira, Eduardo Hochuli [UNESP]; Pereira-Filho, Valfrido Antonio [UNESP] (Wolters Kluwer, 2021)
OBJECTIVES: This study evaluated the bone quality of the maxilla and mandible by using the classification proposed by Lekholm and Zarb (L & Z) and histomorphometry. METHODS: Sixty edentulous areas were evaluated. The classification by L & Z was obtained through the evaluation of periapical and panoramic radiographs associated with the surgeon's tactile perception during milling and implant installation. Before implant installation, bone biopsies of standardized sizes were performed for histological evaluation. RESULTS: Type III bone quality was more frequent in the posterior (73.33%) and anterior (73.33%) maxilla, whereas type II bone quality was more frequent in the posterior (53.33%) and anterior (60.00%) mandible. Through histometry, statistical difference was observed for the amount of bone tissue of the posterior region of the maxilla in relation to the anterior and posterior regions of the mandible (P ≤ 0.043). However, there was no difference in osteocyte counts between alveolar regions (P = 0.2946). In the female gender, the age showed a low positive correlation with the L & Z classification (rho = 0.398; P = 0.006) and in the male gender, a moderate negative correlation was observed (rho = -0.650, P = 0.016). CONCLUSIONS: Both methods detected differences in the bone quality of the alveolar regions of the maxilla/mandible and that the classification by L & Z is a reliable method, since it was consistent with histomorphometry, considered the gold standard method for the evaluation of bone quality and greater bone density was observed in older men.